Perancangan Perabot Kerja Kantor dengan Kombinasi Fungsi Bidang Kerja, Fungsi Penyimpanan, dan Fungsi Wadah Tanaman - Arvelina Sugiharto; Yusita Kusumarini; M. Taufan Rizqy (Intra, 2016)
The increasing modern life requires people to keep working. Not all environments brings positive impact, but also negative impact, one of them is Sick Building Syndrome. SBS is a health nuisance that relates with a person's duration inside the office building. Putting plants into rooms is one of the SBS solution. But the plants' existence may also cause new problems for the working space. It requires a solution which is able to put plants into a room without cutting a lot of spaces, by adhering to the values of health, efficiency and effectiveness. As basic workmanship, the design thinking by David Kelley adopted into several stages which are initial stage (empathize), determination stage (define), idea finding stage (ideate), trial stage (prototype), and implementation (test). This design has 3 sets of irrigation system, which are independent irrigation, irrigation by user, and watering by others than the user. This third system is intended for ease and efficiency to users of related furniture. Besides, its preferred for the health value which want to be achieved with the presence of plants.